Odetta zekiergeni a new species of Pyramidellidae (Mollusca: Gastropoda) from the eastern Mediterranean Sea - Öztürk, Bilal (Zootaxa, 2013)
During the past decades intensive investigations on the zoobenthic fauna of Izmir Bay have been carried out (Çınar et al., 2012). This area has suffered from intense pollution due to the influx of untreated wastes of different origin. Until the year 2000, the inner part of Izmir Bay, where the Alsancak harbour is located, has been considered as one of the most polluted areas in the Mediterranean Sea. Recent studies performed in the area (Çınar et al., 2006; Ergen et al., 2006) showed that a number of species of alien or native origin have gradually re-colonized the area after the establishment of a wastewater treatment station  within “The Grand Canal Project” on February 2000. Since then Çınar et al. (2012) have reported 417 species from the area including 13 alien taxa in a study of the zoobenthic organisms inhabiting the soft substrate in Izmir Bay.